Pathogenic Factors and Prognosis of De Novo Aneurysms After Aneurysm Clipping. Issue 6 (30th September 2022) - Lu, Zhuangzhuang; Wang, Chao; Tang, Fengjiao; Feng, Yugong
Abstract : Objective: To confirm this hypothesis, this study aimed to explore the pathogenic factors, prognosis, and their relationship in de novo aneurysms and to reach a consensus on their management. Methods: First, the clinical data of 5 patients with de novo aneurysms from April 1998 to October 2021 were analyzed retrospectively. Then, the English literature on de novo aneurysms reported in Pubmed from 1985 to 2021 was systematically reviewed, and 18 case reports from 17 articles and 16 case series were identified. Univariate and multivariate analyses and modified Fisher test were used to analyze the relationship between pathogenic factors and prognosis. Results: Hypertension was noted in 60% of our clinical cases, 50% of the case series identified in the literature review, and 66.7% of the case reports in the literature review. In the case reports identified from our literature review, the proportion of original aneurysms in the anterior circulation was 96.3%. Moreover, in our 5 cases, all original aneurysms occurred in the anterior circulation. The rupture rate of original aneurysms in our 5 cases was 100%, and that of the cases reported in the literature review was 88.9%. Univariate logistic analysis showed that the time interval was related to the prognosis of de novo aneurysms with a P value of 0.048 and an odds ratio of 0.968 (95% confidence interval 0.938–1.000). Modified Fisher exact tests showed that patient age at the occurrence of de novo aneurysm P = 0.029) was related to the prognosis of de novo aneurysms. Conclusions: Hypertension, an original aneurysms located in the anterior circulation and rupture represent the pathogenic factors associated with de novo aneurysms. The time interval to de novo aneurysm and patient age at the occurrence of de novo aneurysm are predictive of prognosis. Based on the above information, we can prevent and improve the prognosis of de novo aneurysms.